Pengolahan dan Pemanfaatan Limpahan Air Sungai Sahang sebagai Air Bersih Untuk Keperluan Laboratorium Teknik Kimia Jurusan Teknik Kimia Politeknik Negeri Sriwijaya - Ahmad Bustomi (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
Clean water is the primary need of living things because water plays an important role in the process of life. The quality of raw water from various sources has different quality and quantity characteristics, which means that not all regions have a clean water supply that can be processed into water suitable for consumption in accordance with clean water standards that meet clean water requirements. Therefore, in processing and utilizing overflow of Sahang River water, the WTP (Water Treatment Plant) system is to remove metals, organic substances and bacteria in accordance with clean water quality standards of the Ministry of Health of the Republic of Indonesia. The stages in the processing and utilization of the Sahang River water overflow are preliminary analysis of samples in the intake, sedimentation and reservoir tanks. Then to ensure the results of processing and utilization of the Sahang river water overflow, we took a comparative sample, namely PDAM Tirta Musi Palembang water. Analysis of physical, chemical and biological parameters. In the analysis test, the physical parameters of clean water include temperature, color, turbidity, dissolved solids (TDS), smell and taste. In the analysis of clean water chemical parameters, including pH, hardness, chloride, organic substances, ammonia, sulfate, nitrite, nitrate, chromium, cadmium, iron, manganese, copper, aluminum, zinc and lead. Meanwhile, the biological parameter analysis test includes the analysis of E-Coli bacteria. The results of the water quality analysis test for WTP (Water Treatment Plant) have been proven to comply with SNI quality standards for clean water with the optimum results obtained in the addition of a coagulant with a concentration of 75 ppm. However, there are parameters that have decreased and increased levels in each type of parameter such as parameters Turbidity (4.27 NTU), pH (7.01), TDS (24.1 ppm), NaCl (49.7 ppm), DO ( 6.95 ppm), Conducto (1.6211 µs) and hardness (13.29 ppm), but it is still within the standard of clean water quality, which means that the Water Treatment Plant (WTP) system is proven to be implemented especially for water purposes. Laboratory of the Department of Chemical Engineering, State Polytechnic of Sriwijaya and generally for the needs of the community at an economical price and good quality